2008
DOI: 10.1002/eji.200838354
|View full text |Cite
|
Sign up to set email alerts
|

A subset of IL‐10‐producing γδ T cells protect the liver from Listeria‐elicited, CD8+ T cell‐mediated injury

Abstract: Although cd T cells play a role in protecting tissues from pathogen-elicited damage to bacterial, viral and parasitic pathogens, the mechanisms involved in the damage and in the protection have not been clearly elucidated. This has been addressed using a murine model of listeriosis, which in mice lacking cd T cells (TCRd -/-) is characterised by severe and extensive immune-mediated hepatic necrosis. We show that these hepatic lesions are caused by Listeria-elicited CD8 + T cells secreting high levels of TNF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(55 citation statements)
references
References 70 publications
0
55
0
Order By: Relevance
“…For extracellular bacteria, antibodies can play a fundamental role in the establishment of protective immunity by neutralizing and opsonizing bacterial antigens [74]. A recent report has shown that the establishment of antibody-secreting plasma cells during bacteria infection requires secretion of IL-21 by bacteria-specific CD4 + T cells [75]. On the other hand, protective immunity against intracellular pathogenic bacteria requires preferably the expansion and activity of effector T cells that contribute to the bactericidal capacity of macrophages and other phagocytic cells.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…For extracellular bacteria, antibodies can play a fundamental role in the establishment of protective immunity by neutralizing and opsonizing bacterial antigens [74]. A recent report has shown that the establishment of antibody-secreting plasma cells during bacteria infection requires secretion of IL-21 by bacteria-specific CD4 + T cells [75]. On the other hand, protective immunity against intracellular pathogenic bacteria requires preferably the expansion and activity of effector T cells that contribute to the bactericidal capacity of macrophages and other phagocytic cells.…”
Section: Introductionmentioning
confidence: 98%
“…Activation and effector function of T cells must be tightly regulated to prevent excessive inflammatory tissue damage during bacterial clearance and subsequent bacterial encounters. It has been shown that, by secreting IL-10, gamma-delta T cells can significantly contribute at controlling T cell proliferation and effector activity after bacterial infection [75]. In addition, production of IL-10 by CD8 + T cells can also contribute at modulating the expansion of memory T cells that are specific for intracellular bacteria [76,77].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, unconventional lymphocytes such as cd T cells appear to act more as regulators of local effector immune responses by delivering rapid stress-surveillance responses triggered by threats to tissue integrity. These responses, which can be elicited by pattern-recognition receptors independently of the T cell receptor (TCR), appear to be extremely pleiotropic and result in a variety of local and systemic effects, some of them immunoregulatory by limiting deleterious ab T cell responses [2][3][4]. In contrast to ab T cells, the contribution of cd T cells to the effector and/or regulatory arms of the alloimmune response are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Vγ4 cells have a substantiated role in both inflammation and tumor surveillance, and are capable of producing IL-17 and IFN-γ (4,8). Vγ1 cells show a suppressive phenotype through the production of TGF-β and IL-10 (4,9,10). In humans, Vγ9Vδ2 and Vδ1 + cells are both present, but depending on the tumor type, one subset can be predominant over the other (7,11,12).…”
Section: Gammadelta (γδ) T Cells In Cancermentioning
confidence: 99%
“…γδ T cells portray a Treg like phenotype by having the capability to produce more conventional suppressive cytokines including IL-10 and TGF-β in order to inhibit αβ T cell immune responses (10,28,44–46). In mice, an accumulation of IL-10 and TGF-β producing γδ T cells resulted in much lower adaptive and NK anti-tumor responses (46).…”
Section: Tumor Promotion By Of γδ T Cellsmentioning
confidence: 99%